Pengembangan Modul Ajar Pemrograman Web Dengan Konsep Scientific Berorientasi Project Based Learning di SMK Negeri 2 Seririt - Sri Addalena, Ketut; Eka Damayanthi, Luh Putu; Seri Wahyuni, Dessy; Agus Wirawan, I Made (Universitas Pendidikan Ganesha, 2018)
This research aims to(1) Design instructional module program concepts scientifict orientation site with project based learning. (2) Implementing Instructional Module Programming the Web with Scientifict oriented concept of Project Based LearningThis type of research use in this study is the research ad development (Research and development or R & D). With the model ADDIE (Analysis,Desaign,Development,Implementation,Evaluation). This research involve multimedia students of SMK Negeri 2 Seririt on academic years 2014/2015.Data of student learning resource obtained by using interviews. Validation of web program teaching module obtained by using questionnaires.the data obtained are analyzed descriptively.Teaching module development web programming with PJBL oriented scientific concept. The results of the data analysis of student responses indicate the student to provide an assessment with an average percentage of 89%, so if the percentage is converted into a good qualification.